Analisis Iklim Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan - Ahmad Faisal Hadziq; budiman budiman (STAI La Tansa Mashiro, 2023)
This study aims to determine: (1) the condition of the work environment at the National Amil Zakat Agency (BAZNAS) of Lebak Regency, (2) employee performance at the National Amil Zakat Agency (BAZNAS) of Lebak Regency, and (3) is there an influence between the work environment on employee performance at the National Amil Zakat Agency (BAZNAS) of Lebak Regency. This research is a correlational quantitative research using simple linear regression analysis. The population in this study were all employees of the National Amil Zakat Agency (BAZNAS) of Lebak Regency, totaling 22 employees. Probability sampling was taken by using simple random sampling technique with a sample of 22. The results showed the following. (1) The condition of the work environment at the National Amil Zakat Agency (BAZNAS) of Lebak Regency, falls into the good category with the categorization results, namely 11 who stated good. (2) Employee performance at the National Amil Zakat Agency (BAZNAS) of Lebak Regency, falls into the good category with the results of categorization, namely 10 who stated good. (3) There is a positive and significant influence between the work environment and employee performance at the National Amil Zakat Agency (BAZNAS) Lebak Regency, with a correlation coefficient (R) of 0.548 and a coefficient of determination of 0.300. This means that 30% of employee performance at the National Amil Zakat Agency (BAZNAS) of Lebak Regency is influenced by the work environment, while the other 70% is determined by other variables not explained in the study.Keywords: work environment, employee performance.